2004
DOI: 10.1097/00007435-200406000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Real-Time Polymerase Chain Reaction Assay for Detection and Quantification of Herpes Simplex Virus Type 1 and Herpes Simplex Virus Type 2 in Genital and Cutaneous Lesions

Abstract: Real-time PCR is a sensitive method for diagnosing genital herpes, and the duplex format is convenient for typing. The method increased the detection rate by 27% compared with virus culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…The principle of qPCR has been described elsewhere (27), as has the design of primers and probes for HSV-1 and HSV-2 detection (20). In brief, the qPCR was carried out using a degenerate primer pair specific for the glycoprotein G gene (HSV-2) and both the G glycoprotein gene and the J glycoprotein gene (HSV-1): forward primer (HSV-1, 5=-GGC CTG GCT ATC CGG AGA-3=; HSV-2, 5=-AGA TAT CCT CTT TAT CAT CAG CAC CA-3=) and reverse primer (HSV-1, 5=-GCG CAG AGA CAT CGC GA-3=; HSV-2, 5=-TTG TGC TGC CAA GGC GA-3=).…”
Section: Figmentioning
confidence: 99%
“…The principle of qPCR has been described elsewhere (27), as has the design of primers and probes for HSV-1 and HSV-2 detection (20). In brief, the qPCR was carried out using a degenerate primer pair specific for the glycoprotein G gene (HSV-2) and both the G glycoprotein gene and the J glycoprotein gene (HSV-1): forward primer (HSV-1, 5=-GGC CTG GCT ATC CGG AGA-3=; HSV-2, 5=-AGA TAT CCT CTT TAT CAT CAG CAC CA-3=) and reverse primer (HSV-1, 5=-GCG CAG AGA CAT CGC GA-3=; HSV-2, 5=-TTG TGC TGC CAA GGC GA-3=).…”
Section: Figmentioning
confidence: 99%
“…While previous reports have shown that laboratory-developed PCR assays are more sensitive than culture for the diagnosis of HSV in dermal and genital samples (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), no prior studies have analyzed the performance characteristics of the Simplexa HSV 1 & 2 direct PCR assay (Focus Diagnostics, Cypress, CA), a new commercial assay that can be performed directly on clinical samples in a nonmolecular laboratory.…”
mentioning
confidence: 99%
“…The quantification of HSV genomes by real-time PCR in genital fluid has been previously reported in a few studies (3,16,34,35,41), but no published procedure has been validated yet. We have herein validated a laboratory-developed one-step real-time PCR assay to quantify accurately HSV DNA in cervicovaginal fluid by using as standard a plasmid containing HSV DNA polymerase target.…”
Section: Discussionmentioning
confidence: 99%